The Effect Of Sugar Concentration on the Organoleptic Quality of Liberika Tungkal Jambi Instant Coffee - Mursalin, Mursalin; Nizori, Addion; Rahmayani, Irma (Department of Technology of Agricultural product (THP) Jambi University, 2019)
Abstract— This study aimed to determine the effect of sugar concentration on the organoleptic quality of instant coffee of Liberika Tungkal Jambi and to determine the optimal concentration of sugar in producing instant coffee with the best organoleptic quality. Instant coffee was produced by co-crystallizationmethod.The crystallizing agent used was granulated sugar. Coffee extract was made using an extractor in a ratio of coffee powder/hotwater of 1/15. Five levels of sugar concentration (15, 25, 35, 45 and 55%) were applied in a completely randomized design with 4 replications. The parameters observed were the sweetness level, the distinctive aroma of coffee, the granulestexture, and the panelist's preference.The parameters were organoleptically determined using 15 trained panelists in the scoring test format. The data was analyzed using ANOVA and DNMRT at 95% confidence level. The results showed that the sugar concentration had a significant effect on the level of sweetness, the distinctive aroma of coffee, and instant coffee granules performance but had no significant effect on solubility and panelist preferences. The optimal sugar concentration to produce instant coffee with good quality was 25%. Keywords— libtukom, instant coffee, recrystallization, sugar